Case Report: Low-Dose Apatinib in the Treatment of Intrahepatic Biliary Cystadenoma With Recurrence and Malignant Transformation - Yang, Yongguang; Mai, Weiheng; Chen, Weifeng; Yang, Chao; Li, Mingyi; Liu, Lijuan (Frontiers in Oncology, 2021)
Apatinib is a new oral tyrosine kinase inhibitor that targets vascular endothelial growth factor receptor-2. It has been proven effective in treating multiple solid tumors. Herein, we report the case of a 67-year-old Chinese patient who was diagnosed with recurrent and malignant transformation of intrahepatic biliary cystadenoma. After multidisciplinary team discussion, the team considered that the remaining liver volume was insufficient for surgical resection. The patient refused chemotherapy and radiotherapy and was willing to take apatinib. Initially, the patient experienced severe tongue ulcers and difficulty eating. The dose of apatinib was then adjusted to 250 mg/day. To date, he has been taking apatinib for 48 months. Regular re-examination showed that the tumor had significantly decreased in size. On January 16, 2021, a CT scan revealed a tumor diameter of 4.5 cm. In our case, the patient achieved partial response and progression-free survival(PFS) of 48.0 months. During treatment, the patient’s appetite and mental state were expected. The treatment did not induce hypertension, fatigue, hand-foot syndrome, or liver and kidney damage. Apatinib may be an option for the treatment of advanced intrahepatic biliary cystadenocarcinoma. Its toxicity is controllable and tolerable. The exact curative effect still needs to be evaluated in more cases.